pk002449: Children in Apartheid South-Africa - International Defence and Aid Fund for Southern Africa; Bloom, Steve
"Prentbriefkaart in zwart-wit voorstellend kinderen in een sloppenwijk, ergens in Zuid-Afrika. Tekst : Squatter camps are a result of South Africa's migrant labour system and are illegal. Living conditions are extremely poor and a child's life is made insecure by the constant threat of the settlement's demolition, the arrest of parents and dispersal of families. Anti-apartheid. FULL TEXT AVAILABLE AT AMSAB-ISH"